PP20 The introduction of simulation software – the student view. (10th November 2020) - Jones, Gaynor Lawson; Lawal, Olan; Cherrill, Richard; Mercer, Sarah; York, Helen
Abstract : Introduction: Traditional simulation has been utilised in the Diagnostic Radiography and Imaging programme at a regional University in the UK for many years. The use of roleplay and x-ray phantoms is a useful addition to bolster student understanding but is staff intensive with large cohorts (100+) and limited facilities. Recently acquired simulation software has allowed students the opportunity to enhance their learning through virtual positioning and imaging. Improvement in technical skills is well documented in literature, 1–4 however student opinion of the usefulness of the software, in enhancing their learning has not been widely researched. Methods: A group of year one diagnostic radiography students (n= 7) were recruited to participate in a focus group, with all participants having had the opportunity to attend five hours of virtual imaging with the new software. Semi-structured questions were used to gather opinions on the use of simulation software within a radiographic technique module. Responses were recorded and transcribed with emergent themes collated. Results: Emergent themes showed students felt they required more initial support with the software and additional time to master the controls. Students felt it was very useful as it gave them the opportunity to produce and review their own images and therefore see the effect of the exposure factors and their positioning, something that would not otherwise be possible with the existing practical lab sessions. Students indicated they found the software useful and their confidence was increased after using the programme. Discussion and Conclusion: Participants had a varied experience initially as some were not familiar with 'gaming style' controls which are needed to operate in the virtual radiography room. Those who were comfortable with the software were able to successfully use it almost immediately. Concern was noted regarding the 'hands off' approach of some supervising tutors, leading to frustration at using the programme, however, the value of the software was noted by all participants. References: Bridge P, Gunn T, Kastanis L, Pack D, Rowntree P, Starkey D. Wilson-Stewart, K. The development and evaluation of a medical imaging training immersive environment. Journal of Medical Radiation Sciences 2014;61(3):159–165. doi:10.1002/jmrs.60 McNulty JP, Rainford L, Bezzina P, Henner A, Kukkes T, Pronk-Larive D, & Vandulek C. A picture of radiography education across europe. Radiography 2015; 2016(1);22:5–11. doi:10.1016/j.radi.2015.09.007 Sapkaroski D, Baird M, Mundy M, Dimmock MR. Quantification of student radiographic patient positioning using an immersive virtual reality simulation. Simulation in Healthcare: The Journal of the Society for Simulation in Healthcare 2019;14(4):258–263. doi:10.1097/SIH.0000000000000380 Shanahan, M. ( 2016). Student perspective on using a virtual radiography simulation. Radiography, 22(3), 217–222. doi:10.1016/j.radi.2016.02.004